Electronic Word Of Mouth Saat Penjualan Live Streaming Shopee Dalam Meningkatkan Impulse Buying - Purbasari, Dewi Maharani; Respati, Mutia Raras (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Technological developments have developed so rapidly and have influenced changes in people's lifestyles towards digital. e-commerce is the electronic trading of goods or services via the Internet and social media. The e-commerce that had the most visitors during the first quarter of 157.97 million was Shopee. Shopee not only provides infrastructure for sellers and buyers to transact but also presents various innovative features to improve the online experience. One feature that is increasingly popular on Shopee is live streaming media, where sellers can broadcast live to promote their products to potential buyers. The purpose of this research is to determine the influence of Electronic Word of Mouth on Impulse Buying, to determine the influence of Live Streaming Sales on Impulse Buying, to determine the influence of Electronic Word of Mouth and Live Streaming Sales together on Impulse Buying. This research uses quantitative methods with a descriptive research approach. With respondents fromÂ  University Â Pakuan students. The selection of respondents was carried out using a purposive sampling method with a total of 100 respondents based on the Slovin formula calculation. Data collection was carried out through questionnaires and the analysis method used was descriptive analysis, with multiple linear regression testing with the SPSS program. The research results show that Electronic Word of Mouth has a significant effect on Impulse Buying, live streaming has no significant effect on Impulse Buying, and Electronic Word of Mouth and Live Steaming has a significant effect on impulse buying simultaneously.